Documentation of science and technology heritage: a collaboration case between the Federal University of Pará and the Evandro Chagas Institute Museum (Cadernos de Sociomuseologia, 2023)
It is nearly impossible to consider the management of cultural spaces without contemplating the potential implementation of informational benefits. The feasibility study and implementation of Tainacan is a solution adopted in the museum field by the Brazilian Institute of Museums, and using it allows the interoperability of museum information throughout the national cultural system. The objective is to report the adversities and institutional solutions experienced in order to present museological documentation solutions for scientific collections within the scope of the heritage of science and technology. The methodology used to achieve the objective was the implementation of the extension project Organization and Management of Museological Documentation of the collections present in the Museum of the Instituto Evandro Chagas. This creates a laboratory of museological documental practices based on research to support the organization and representation of information of the Evandro Chagas Institute's museological collection, also allowing semantic conceptual modeling according to international standards for digital collections. This university extension action provides a unique and essential professional experience for students and opportunities for the dissemination of the profession and the Museology Course at the Universidade Federal do Pará through the work carried out.KEYWORDS: Museum Documentation; University Extension; Heritage of Science and Technology